Modelling of the binding of TRPV1 receptor to capsaicin, capsazepine and related agonists and antagonists - İnce, Büşra. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Capsaicin is a natural compound found in hot pepper and is an agonist of the receptor protein TRPV1 (Transient Receptor Potential Vanilloid) in dorsal root ganglia. TRPV1 is responsible for pain and heat perception. Capsazepine is a synthetic compound and is the first known antagonist of TRPV1; it interferes with the binding of capsaicin to TRPV1 in order to prevent protein activation and the resulting pain sensation. In this study, multiple conformations of capsaicin and capsazepine are docked to the active site of TRPV1 protein with rigid docking by Autodock4 to find which conformations give the lowest binding energy. We also observe analog molecule results in similar conformation conditions. The consistency of the results is checked by comparison with analog molecule binding. Agonists like resiniferatoxin, gingerol, nonivamide, nordihydrocapsaicin, and 6-shogaol and antagonist; sb-366791 is chosen as the analog molecules. The docking results of gingerol, shogaol, dihydrocapsaicin, nonivamide, and sb366791 had similar binding energies. Nordihydrocapsaicin and resiniferatoxin gave better binding energies in their capsaicin-like conformations. In general, all analog molecules are observed to make more hydrogen bonds with the protein.
Keywords: Analgesics.; TRP channels.; Nervous system -- Degeneration.